Öffentliches Verkehrsangebot in ländlichen Räumen. Gestaltungsmöglichkeiten und Auswirkungen auf die Lebensqualität. - Meschik, Michael; Meth, Dagmar (Oekom, 2008)
Die Versorgung ländlicher Räume mit öffentlichem Verkehr wird immer schlechter - zum Leidwesen all jener, die über kein Auto verfügen. Bedarfsgesteuerter öffentlicher Verkehr, durch den Versorgungseinrichtungen leichter erreichbar werden, steigert die Lebensqualität.

The accessibility of destinations in rural areas via public transport is generally poor, if possible at all. The lack of public transport deprives individuals, who cannot or do not want to use a private car, of a certain quality of life. The obligation of public transport to be cost efficient leads to further reductions in the service quality and to further decreases in the accessibility of friends and relative, grocers, health ser-vices, education and recreation facilities. The European research project 'Actions on the integration of Rural Transport Services' (ARTS) investigated innovative public transport l solutions particularly in scarcely populated areas. Projects in eight European regions were implemented and evaluated, six of which resulted in demand responsive transport initiatives or public transport linked with school transport. The examples show that improvements in public transport can be achieved, but must be tailored to the local situation. For those without access to a car, being able to maketrips by public transport is valued as important to their quality of life and helps to sustain social life in the rural areas.
Public Transport in Rural Areas - Possible Solutions and Effects on Quality of Life.
Keywords: Verkehr; Regionalverkehr; ÖPNV; Schülerverkehr; Ländlicher Raum; Mobilität; Lebensqualität; Verkehrsbedienung; Verkehrsverhalten; Forschungsprojekt; Befragung; Auswertungsmethode; Bedarfsverkehr; Barrierefreiheit; Mobilitätsmanagement; Modellprojekt